FIC proteins: from bacteria to humans and back again. Issue 2 (22nd February 2018) - Veyron, Simon; Peyroche, Gérald; Cherfils, Jacqueline
Abstract: During the last decade, FIC proteins have emerged as a large family comprised of a variety of bacterial enzymes and a single member in animals. The air de famille of FIC proteins stems from a domain of conserved structure, which catalyzes the post-translational modification of proteins (PTM) by a phosphate-containing compound. In bacteria, examples of FIC proteins include the toxin component of toxin/antitoxin modules, such as Doc-Phd and VbhT-VbhA, toxins secreted by pathogenic bacteria to divert host cell processes, such as VopS, IbpA and AnkX, and a vast majority of proteins of unknown functions. FIC proteins catalyze primarily the transfer of AMP (AMPylation), but they are not restricted to this PTM and also carry out other modifications, for example by phosphocholine or phosphate. In a recent twist, animal FICD/HYPE was shown to catalyze both AMPylation and de-AMPylation of the endoplasmic reticulum BIP chaperone to regulate the unfolded protein response. FICD shares structural features with some bacterial FIC proteins, raising the possibility that bacteria also encode such dual activities. In this review, we discuss how structural, biochemical and cellular approaches have fertilized each other to understand the mechanism, regulation and function of FIC proteins from bacterial pathogens to humans. Abstract : Insight into function and regulation of bacterial, pathogen and animal FIC proteins by combined structural, biochemical and cellular methods fertilized each other to yield new discoveries.